Characteristics and Evolution of China’s Carbon Emission Reduction Measures: Leading Towards Environmental Sustainability - Zhang, Wenyu; Zhang, Changyou; Wei, Songbo; Zhang, Qiang; Rehman, Abdul; Shah, Adeel (Frontiers in Environmental Science, 2022)
The increasing concentration of carbon emission (CE) in the atmosphere, which causes climate change (CC), has become a priority at the global level. The Chinese govt has enacted a series of CE reduction policies and regulations during the recent decades, which have effectively encouraged the country’s green and sustainable growth. For sustainable development and subsequent policy design, it is critical to investigate the features and evolution of CE reduction programs. First, we collected China’s national-level CE reduction policy texts from 2007 to 2021 as research objects. Second, using content analysis and NVivo software, a three-dimensional analytical framework of “Policy tools–Development stages–Policy implementation objects” is developed and investigated based on the theory of policy tools. Finally, the CE reduction policy language is coded line by line using empirical analysis, yielding 725 reference points. The results show that 1) The results show that: 1) in the evolution of CE reduction policy, environmental policy tools are the most used, accounting for 51.17%, and the use of supply-based and demand-based policy tools account for 32.28 and 16.55%, respectively; 2) demand-based policy tools need to be strengthened, and the structure of supply-based and environmental policy tools needs to be adjusted; 3) the govt’s coordination with research institutions and the public is not sufficient The implementation of policy instruments is insufficient; 4) China’s CE reduction policy is gradually developing from a macroscopic single subject policy to a diversified and specific policy with specialized content. Therefore, we recommend optimizing the policy structure in the light of social characteristics and strengthening the government’s guiding role in China’s CE reduction efforts. It is also recommended to increase financial instruments and enhance the binding force of laws and regulations.